Hubungan Asupan Lemak Dan Aktivitas Fisik Dengan TekananDarah Pada Lansia Di Kelurahan Sondakan Surakarta - Hapsari, Aulia Nisa; , Dwi Sarbini, SST., M.Kes (2016)
Introduction: Two factors that can affect blood pressure are low physical activity and axcess intake of fat. Less activities will cause the increase of heart rate, therefore heart has to work harder. Increase of fat intake will increase the levels of fat in the blood, therefore it the accumulation of fat will lead to clogged arteries. Objective: To determine the correlation between fat intake and physical activity and blood pressure in the elderly at the sondakan village surakarta. Method: This study was an observational study with cross sectional approach. 67 subjects through simple random sampling. Physical activity was obtained by physical activity recall, intake of fat was using Semi Quantitative Food Frequency Questionnaire for one month, and blood pressure was obtained from direct measurement using a sphygmomanometer by a midwife. The result shows that Pearson product moment was used for correlation test. Results: The result shows that 91.0% of the subjects had a high fat intake. 65.8% of the subjects had mild physical activity. 76.1% of the subjects had high systolic blood pressure and 53.7% of the subjects had high diastolic blood pressure. Conclusion: No association between fat intake and physical activity and blood pressure in the elderly at sondakan village surakarta. Suggestions: Further research can investigate other factors such as factors that can be controlled include sodium intake, smoking, stress, obesity lifestyle, and medications. Factors that can not be controlled include age, gender, and family history, as well as the presence of other comorbidities such as diabetes mellitus, stroke, coronary heart disease, and kidney failure. Keywords: Blood Pressure, Intake of Fat , Physical Activity Bibliography: 58: 2000-2013